Subsequent somatic axis and bone tissue metabolism responses to a low-zinc diet with or without phytase inclusion in broiler chickens - Muszyński, Siemowit (PLoS One, 2018)
Zinc is required for normal bone development and cartilage formation. The purpose of this study was to assess the effect of with adding organic Zn (alone or phytase inclusion) at the reduced dose to growing male Ross 308 chickens on somatic axis and bone tissue metabolism. 200 one-day old broilers were divided into the negative control group fed diet without Zn or phytase inclusion, positive control group receiving Zn in the 100% of daily recommended dose from ZnO, and two experimental groups fed diet introduced Zn in 25% of daily recommendation as a glycine chelate (Zn-Gly) with or without phytase inclusion (500 FTU·kg(-1)). Supplemental organic Zn increased bone Zn and Mg content, serum IGF-1, growth hormone and leptin concentration. Additional phytase inclusion increased body weight gain, blood plasma Ca, Fe, Zn and osteocalcin concentration and tibia ash percentage when compared to the Zn-deprived control. Bone geometry, yield and ultimate strengths were enhanced in both organic Zn supplemented groups, and the overall mechanical strength parameters of bone were better in these groups than in the positive control group supplemented with standard dose of inorganic Zn. Also marked improvements in the thickness of articular and the growth plate cartilages as well as real bone volume and thickness of metaphyseal trabeculae were achieved in all broilers fed Zn-supplemented diet irrespective of phytase inclusion, however, the highest cancellous bone mass and the best trabecular structure were noted after ZnO supplementation. In concludion, although dietary organic Zn given to growing broilers in 25% of daily recommended dose improved general bone properties and mechanical strength, the obtained results do not allow to unambiguously state that organic Zn supplementation at this level, even after phytase inclusion, is sufficient for proper bone development.